Ruang Publik-Digital yang Bertanggungjawab: Sebuah Tantangan - Tukina (INDO PUBLISHING, 2025)
Human life continues to change, develop, and produce new orders. In the end, the new order gave birth to life in today's digital public space. Digital public space is developing towards a better life. . The development of technology in digital public space rise to many problems. These various problems give rise to challenges in digital public space. The development of public space is so rapid on the one hand, but not the others. This situation creates challenges in public spaces that are difficult to address. The relatively low level of education have basic challenges. And another problem is the awareness that public space has positive and negative impacts that need to be widely known. and understood by the community. Public space awareness can harm oneself, others, and society to the state needs to be properly realized. Awareness of negative risks after experiencing something bad, very detrimental to oneself and one's family. Awareness of responsible public space need to be continuously socialized so that public space can run well